2016
DOI: 10.1016/j.rbre.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes in dermatomyositis and polymyositis

Abstract: We showed distinct ECG changes between DM and PM and a higher frequency of LVH in patients compared to controls. Investigation of cardiac involvement should be considered even in asymptomatic patients, especially PM. Further studies are necessary in order to determine the correlation of ECG findings with other complementary tests, clinical manifestations, disease activity and progression to other cardiac diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
0
14
0
4
Order By: Relevance
“…with PM than in DM patients [27]. A correlation between ECG abnormalities and disease progression has not been established.…”
Section: Skin Signs Such As Heliotropic Erythemamentioning
confidence: 93%
“…with PM than in DM patients [27]. A correlation between ECG abnormalities and disease progression has not been established.…”
Section: Skin Signs Such As Heliotropic Erythemamentioning
confidence: 93%
“…Devezy et al. found that in a group of 34 PM patients, VES was diagnosed in two patients based on the resting electrocardiogram (5.9%) (Deveza et al., ). In the study of Taylor et al.…”
Section: Discussionmentioning
confidence: 99%
“…Devezy et al found that in a group of 34 PM patients, VES was diagnosed in two patients based on the resting electrocardiogram (5.9%) (Deveza et al, 2016). In the study of Taylor et al premature ventricular extrasystoles were observed in 69% of patients and 31% of patients reported palpitations as a symptom (Taylor et al, 1993).…”
Section: Case Reportmentioning
confidence: 97%
“…Therefore, all individuals should be referred for cardiac and lung function assessment at the time of diagnosis of SAM, and clinical evaluation, including detailed anamnesis and physical examination is essential [108]. Some tests are recommended, such as electrocardiogram and the evaluation of pulmonary function, to verify cardiac involvement with arrhythmias and conduction abnormalities and impairment of pulmonary function as a reduction in vital capacity (B) [90,112] (C) [85] (D) [113].…”
Section: Literature Review and Analysismentioning
confidence: 99%